Establishing the accuracy of density functional approaches for the description of noncovalent interactions in ionic liquids. Issue 45 (16th November 2021) - Kim, Minho; Gould, Tim; Izgorodina, Ekaterina I.; Rocca, Dario; Lebègue, Sébastien
Abstract : We test a number of dispersion corrected Generalized Gradient Approximation (GGA) and meta-GGA functionals for their ability to predict the interactions of ionic liquids, and show that most can achieve energies within 1 kcal mol −1 of benchmarks. Abstract : We test a number of dispersion corrected versatile Generalized Gradient Approximation (GGA) and meta-GGA functionals for their ability to predict the interactions of ionic liquids, and show that most can achieve energies within 1 kcal mol −1 of benchmarks. This compares favorably with an accurate dispersion corrected hybrid, ωB97X-V. Our tests also reveal that PBE (Perdew–Burke–Ernzerhof GGA) calculations using the plane-wave projector augmented wave method and Gaussian Type Orbitals (GTOs) differ by less than 0.6 kJ mol −1 for ionic liquids, despite ions being difficult to evaluate in periodic cells – thus revealing that GTO benchmarks may be used also for plane-wave codes. Finally, the relatively high success of explicit van der Waals density functionals, compared to elemental and ionic dispersion models, suggests that improvements are required for low-cost dispersion correction models of ions.